02.27 Myostatin-induced mechanisms of inflammatory bone destruction by invasive fibroblast-like synoviocytes. (1st March 2017) - Fennen, Michelle; Kracke, Vanessa; Varga, Georg; Pap, Thomas; Dankbar, Berno
Abstract : Background: Myostatin, a secreted member of the transforming growth factor-β (TGF-β) family, is predominantly expressed in skeletal muscle and negatively regulates muscle growth. We previously demonstrated that myostatin deficiency leads to reduced joint inflammation and joint destruction in arthritic human TNF transgenic mice (Mstn -/- hTNFtg). Additionally, myostatin was highly expressed in rheumatoid arthritis (RA) synovial tissues with most prominent staining of synovial fibroblasts (FLS). Moreover, further studies have shown that myostatin participates in the complex interplay of inflammatory cytokines, increasing tissue and systemic levels of IL1, IL6 and TNFα. Here we investigate the regulatory role of myostatin on joint inflammation and inflammatory cytokine expression in the development of RA. Material and methods: Immunophenotyping of isolated spleen and bone marrow derived cells of wt, Mstn -/-, hTNFtg and Mstn -/- hTNFtg mice was performed by FACS analysis. Moreover, hTNFtg mice with a Col1α2-specific deletion of myostatin (Col1α2-Cre/Mstn fl/fl hTNFtg) were generated and clinical severity and histological changes were determined by μCT and histomorphometry. Effects of myostatin on the secretion of IL-6 by human and mouse FLS and the expression of Interleukin-17 receptor C (IL-17RC) were evaluated by ELISA and western blotting. The secretion of various cytokines/chemokines by FLS of Mstn -/- hTNFtg and hTNFtg mice was investigated using a specific antibody array. Results: In vivo, the bone marrow of Mstn -/- hTNFtg mice showed a decreased number of B-cells compared to control mice, which might influence the development of the disease. Moreover, comparison of hTNFtg mice, which exhibit a Col1α2-specific deletion of myostatin, with hTNFtg control mice, lead to decreased bone destruction and inflammation examined by µCT and histomorphometric analysis. In vitro, stimulation of FLS with myostatin enhanced the IL-17-mediated secretion of IL-6 by FLS through upregulation of the IL-17RC. Furthermore, analyses of IL-17-mediated cytokine regulation revealed differences in the secretion profile of cytokines/chemokines between FLS of Mstn -/- hTNFtg and FLS of hTNFtg control mice, suggesting that myostatin is involved in the regulation of joint inflammation. Conclusion: These data suggest that myostatin could be an indirect regulator of cytokine expression by FLS, associated with enhanced inflammation and thus promote joint destruction during chronic inflammatory arthritis.